Habitual water intake impacted the body composition of young male athletes in free-living conditions: a cross-sectional study - Jianfen Zhang; Jianfen Zhang; Na Zhang; Na Zhang; Yibin Li; Hairong He; Ge Song; Junying Chen; Junying Chen; Yi Yan; Guansheng Ma; Guansheng Ma (Frontiers Media S.A., 2024)
The study aimed to explore the associations between water intake and body composition and differences of body composition in different water itake and hydration statuses among young male athletes. A cross-sectional study was conducted among 111 young male athletes in Beijing, China. Total drinking fluids (TDF) and water from food were assessed using a 7-day, 24-h fluid intake record questionnaire and the duplicate portion method, respectively. The osmolality of 24-hour urine and blood samples was tested. Body composition was measured using a bioelectrical impedance analyzer twice at 5-min intervals. Participants were divided into two groups based on the recommendations of total water intake (TWI) and TDF in China, as well as into three groups based on 24-h urine osmolality. Pearson's correlation coefficients were calculated to determine the relationship between water intake and body composition. Chi-square tests and Student's t-tests were used to compare differences. A total of 109 participants completed the study. TDF (r = 0.230, p = 0.016; r = 0.234, p = 0.014; r = 0.242, p = 0.011) and TWI (r = 0.275, p = 0.004; r = 0.243, p = 0.011; r = 0.243, p = 0.011) were positively correlated with total body water (TBW), intracellular water (ICW), and extracellular water (ECW). TBW/body weight (BW) was positively associated with TDF percentage of BW (TDF/BW) (r = 0.267, p = 0.005), water from food percentage of BW (r = 0.217, p = 0.024), and TWI percentage of BW (TWI/BW) (r = 0.316, p = 0.001). Participants who met the TDF recommendation of China had 1.3 kg higher skeletal muscle mass (SMM), 0.9 kg higher ICW, and 0.5% higher TBW/BW than those who did not (all p < 0.05), with fat-free mass (FFM) and TBW being higher (p = 0.051; p = 0.050). Those who met the TWI recommendation of China had 1.3 kg higher SMM, 2.4 kg higher FFM, 1.1 kg higher ICW, 0.6 kg higher ECW, and 1.7 kg higher TBW than their counterparts (all p < 0.05). Moderate associations were found between water intake and body composition. No significant differences were observed among participants in three hydration statuses (all p > 0.05). Participants who met the TWI or TDF recommendations had better body composition distribution than their counterparts. Thus, habitual water intake, not hydration status, affects body composition among athletes in free-living conditions.